Teaware and tea art with oriental aesthetics - Chuangeng, Fan; Ming, Zhang ([China] China Arts and Entertainment Group Ltd)
The review of history can find the countless ties between Chinese tea culture and porcelain. Appreciating tea is not only focused on the shape, color, aroma, and taste of tea, but also pays attention to the texture and design of teawares. The teapot is a container of tea, and tea is a way of nurturing the teapot. Over time, teapots have become more than a functional vessel for brewing tea, and have taken on a new role as collectible pieces of art. Different types of tea matches different teapots. Inside of the pot is tea; outside of the pot is tea art
Keywords: Product design; Art -- China